Flexible Tarife in elektronischen Fahrgeldmanagementsystemen und ihre Wirkung auf das Mobilitätsverhalten - Wirtz, Matthias (Schriftenreihe des Instituts für Verkehrswesen, Karlsruher Institut für Technologie, 2014)
Automatic fare collection systems (AFC) in public transportation systems extend the options of price discrimination when arranging tariffs. Using a Conjoint analysis the preferences towards the different types of price discrimination are evaluated and the influences on the mode choice are quantified. In addition to this the flat rate bias which describes the tendency to opt for fixed prices is explained and quantified.